Measurement Properties of the Lower Extremity Functional Scale: A Systematic Review - Mehta, Saurabh P.; Fulton, Allison; Quach, Cedric; Thistle, Megan; Toledo, Cesar; Evans, Neil A. (The journal of orthopaedic and sports physical therapy, 2016)
Systematic review of measurement properties. Many primary studies have examined the measurement properties, such as reliability, validity, and sensitivity to change, of the Lower Extremity Functional Scale (LEFS) in different clinical populations. A systematic review summarizing these properties for the LEFS may provide an important resource. To locate and synthesize evidence on the measurement properties of the LEFS and to discuss the clinical implications of the evidence. A literature search was conducted in 4 databases (PubMed, MEDLINE, Embase, and CINAHL), using predefined search terms. Two reviewers performed a critical appraisal of the included studies using a standardized assessment form. A total of 27 studies were included in the review, of which 18 achieved a very good to excellent methodological quality level. The LEFS scores demonstrated excellent test-retest reliability (intraclass correlation coefficients ranging between 0.85 and 0.99) and demonstrated the expected relationships with measures assessing similar constructs (Pearson correlation coefficient values of greater than 0.7). The responsiveness of the LEFS scores was excellent, as suggested by consistently high effect sizes (greater than 0.8) in patients with different lower extremity conditions. Minimal detectable change at the 90% confidence level (MDC90) for the LEFS scores varied between 8.1 and 15.3 across different reassessment intervals in a wide range of patient populations. The pooled estimate of the MDC90 was 6 points and the minimal clinically important difference was 9 points in patients with lower extremity musculoskeletal conditions, which are indicative of true change and clinically meaningful change, respectively. The results of this review support the reliability, validity, and responsiveness of the LEFS scores for assessing functional impairment in a wide array of patient groups with lower extremity musculoskeletal conditions.